Profiling wound management in the emergency department: A descriptive analysis. Issue 3 (August 2016) - Cross, Rachel; Jennings, Natasha; McGuiness, William; Miller, Charne
Abstract: Background: The service profile of wound, skin and ulcer presentations to emergency departments is an area that lacks an existing published commentary. Knowledge of these presentations would inform the allocation of resources, staff training, and, in turn, patient outcomes. The aim of this study was to describe the discharge and referral status of adult patients presenting to one Australian emergency department with a wound, skin or ulcer condition. Methods: A retrospective descriptive review was conducted of all emergency presentations including discharge and referral statuses for skin, wound and ulcer related conditions from 1st January 2014 until 31st December 2014. Results: A total of 4231 wound, skin and ulcer conditions were managed, accounting for 7% of the total emergency presentations. Wound conditions were the most prevalent (n = 3658; 86%). Males were more likely to present for all three conditions. For all conditions, discharge to home was the most common destination. Following discharge to home, over half all patients were referred to the local medical officer. Conclusions: Nursing workforce models, education and training needs to reflect the skill set required to respond to wound, skin and ulcer conditions to ensure that high quality skin and wound care continues outside of the emergency department.